Pengaruh Kecerdasan Emosi dan Kepribadian Hardiness terhadap Resiliensi Belajar pada Masa Pandemi Pada Siswa MAN Asahan - Lutfiah, Aisyah; Menanti, Asih; Hasanuddin, Hasanuddin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the effect of emotional intelligence and personality hardiness on learning resilience. This research is a quantitative study, using a research sample of 95 people, taken in total from the research population. Sampling with total sampling technique. Data analysis used multiple regression analysis. The results showed that (1) There was a significant positive effect of emotional intelligence on learning resilience, seen from the value of the determinant coefficient (Rx1.y) = 0.633 with p = 0.000 < 0.050, meaning that there was a positive influence of emotional intelligence on learning resilience; (2) There is a significant positive effect of hardiness personality on learning resilience as seen from the value of the determinant coefficient (Rx2.y) = 0.413 with p = 0.000 < 0.050, meaning that there is a positive influence of hardiness personality on learning resilience; (3) there is a significant positive effect of emotional intelligence and personality hardiness on learning resilience seen from the value of the determinant coefficient (Rx1.x2.y) = 0.539 with p = 0.000 < 0.050, meaning that there is a positive relationship between emotional intelligence and personality hardiness on learning resilience. The percentage of contribution given by the influence of emotional intelligence and personality hardiness simultaneously on learning resilience is 29.1%.